Study of failure mechanism of double-lap joints of steel to FRP by bolt and resin - Amir Hossein Zakeri; Asghar Vatani Oskoei; Saeed Madani (Journal of Structural and Construction Engineering, 2017)
In this study, the behavior of joints in two sides of steel coat which are screwed to the composite plate, and joints of two sides of compound steel coat (bolted and bonded) to the composite plate has been studied. In the standards, distance of mechanical bolts from the edges and the distance of mechanical bolts from each other have been discussed. Different distances in the range of the standards determined for the distance of screws from edges and screws from each other. In this paper, the screw joints and the combined joints with different terminal distances for screws from the edges are modeled and studied. The results showed the basic effects of the terminal distance of the screw from the connection edges on the resistance and mechanism of break of screw joints. In combined joints, the terminal distance of the screw had trivial effects in the resistance and mechanism of joint break. In addition, overlap length of the connection elements on increase of joint resistance analyzed and studied. To do so, a combined joint with configuration of two steel plates and one CFRP/GFRP composite plates which were joined by two screws and adhesive layers with different overlap were modeled. The results showed the direct relationship between increase of overlap length and increase in resistance of the joint. Finally, a design guide to be used in practice was proposed.